Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/cctc.202000699
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of the Electron‐Beam Irradiation on Pd/Ga2O3 Catalyst under Ambient Pressure

Abstract: Introducing atmosphere in transmission electron microscope enables to directly observe the structural features of catalyst under working conditions. It offers the possibility to study the microstructural evolution and correlate real structures with catalytic properties at nano‐ or atomic‐scale during catalysis. However, the damages to catalyst derived from the high energy electron‐beam irradiation cannot be ignored and may lead to ambiguous conclusions, as the interaction between reactive gas molecules and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In situ transmission electron microscopy (TEM) is a versatile technique for observing and understanding the dynamic behavior of catalysts in the chemical environment. It enables real-time imaging of the microstructural evolution of catalysts under volatile reaction conditions at the atomic level and corelating the dynamic behavior of catalysts with performance, which is extremely crucial for the structural regulation of catalysts. In particular, the investigation of the thermal stability of the catalysts under the distinct gas environments and elevated temperature conditions is beneficial to realize the controllable preparation of supported catalysts. , Li et al demonstrated the distinct sintering behaviors of Au/TiO 2 catalyst under different atmospheres via environmental TEM (ETEM) and provided the microstructural information on TiO 2 support . Yang et al revealed that Pt NPs supported on graphene oxide preferentially exposed the high-index facets under elevated temperatures, which results in the aggregation of NPs and provides the direct evidence for the thermal instability of the catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…In situ transmission electron microscopy (TEM) is a versatile technique for observing and understanding the dynamic behavior of catalysts in the chemical environment. It enables real-time imaging of the microstructural evolution of catalysts under volatile reaction conditions at the atomic level and corelating the dynamic behavior of catalysts with performance, which is extremely crucial for the structural regulation of catalysts. In particular, the investigation of the thermal stability of the catalysts under the distinct gas environments and elevated temperature conditions is beneficial to realize the controllable preparation of supported catalysts. , Li et al demonstrated the distinct sintering behaviors of Au/TiO 2 catalyst under different atmospheres via environmental TEM (ETEM) and provided the microstructural information on TiO 2 support . Yang et al revealed that Pt NPs supported on graphene oxide preferentially exposed the high-index facets under elevated temperatures, which results in the aggregation of NPs and provides the direct evidence for the thermal instability of the catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the microstructural evolution of Pd 2 Ga was monitored through ETEM at elevated temperatures. Here, electron dose rate less than 300 e·Å 2 s −1 was adopted during the HRTEM observation to avoid the possible damage from the high-energy electron beam according to our previous studies ( 34 ). One identical NP located on the edge of supports was selected to elucidate the ongoing surface variation (fig.…”
Section: Resultsmentioning
confidence: 99%